Acupuncture for migraine: a literature review of neuroimaging studies - Tong, Dan; Yao, Rui; Zhang, Xinyue; Tao, Siyuan; Chen, Nuo; Wu, Wanxia; Wu, Sai; Zhou, Jun; Ren, Yulan; Liang, Fanrong; Pan, Litao; Li, Zhengjie (Frontiers in Neurology, 2025)
BackgroundAcupuncture is effective for migraine treatment with minimal side effects. Neuroimaging techniques have been extensively used to explore the central mechanisms of acupuncture for migraine. This review aims to summarize neuroimaging study of acupuncture for migraine, providing a valuable reference and foundation for future clinical and mechanistic research.MethodsFrom database inception to November 19, 2024, we conducted a comprehensive search of four English-language and four Chinese-language databases. All published clinical controlled trials utilizing neuroimaging methods were included after rigorous screening. This review summarizes the immediate and preventive effects of acupuncture in migraine treatment, as well as the possible neural mechanisms underlying its efficacy in alleviating pain and non-pain symptoms.ResultsA total of 833 papers were identified, and 40 met the inclusion criteria after screening. Among them, 8 studies focused on the immediate effects of acupuncture, while 32 investigated its preventive effects. General, methodological, and neuroimaging data were extracted and summarized. These studies utilized various neuroimaging techniques, including functional magnetic resonance imaging (fMRI), diffusion tensor imaging (DTI), fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT), transcranial Doppler sonography (TCD), and magnetic resonance spectroscopy (MRS). The immediate effects of acupuncture treatment for migraines primarily involve brain regions such as the middle frontal gyrus (MFG), precuneus, and postcentral gyrus, most of which belong to the default mode network (DMN), central executive network (CEN), and salience network (SN). In terms of preventive effects, the key regions involved are the precuneus, anterior cingulate cortex (ACC), MFG, most of which involved in the DMN, SN, CEN, and descending pain modulatory system (DPMS).ConclusionThis systematic review reveals that the brain regions involved in acupuncture treatment for migraine headache include the DMN, SN, CEN, and DPMS, which are related to pain sensation, emotion and modulation. Future research could prioritize meticulously designed, high-quality, multimodal neuroimaging studies to further elucidate the neuroimaging evidence for acupuncture in migraine treatments from different aspects.